Hubungan Self-Control (Kontrol Diri) dan Konformitas Teman Sebaya pada Mahasiswa Wanita yang Mengkonsumsi Rokok Elektrik (Vape) di Kota Bandung - Salma, Illya; Qodariah, Siti (Bandung Conference Series: Psychology Science, 2024)
Abstract. Peer conformity among students who want to consume electronic cigarettes (vapes) in Bandung City is still relatively high, one of the reasons is the low level of self-control. Self-control is a cognitive ability that helps the dynamics of forming a behavior in an individual, low self-control can have an impact on an individual's inability to determine a behavior from various alternative choices such as peer conformity in female students who consume electronic cigarettes (vape) in the city Bandung. This research uses a quantitative approach with correlational methods and uses convenience sampling. The subjects of this research were 103 female students who consumed electronic cigarettes (vapes) in Bandung City. Data collection in this study used the Self Control Scale (SCS) measuring instrument created by Averill (1973) which has been adapted by Nabila (2020) and The Conformity Scale (TCS) created by Sears et al. (2009) which has been adapted by Jessica (2017). The data analysis technique uses the Spearman rank correlation statistical test. The results of data analysis state that there is a significant negative relationship between self-control and peer conformity with values r = -0.544 and p = 0.000. This means that the higher self-control, the lower peer conformity, and conversely, if self-control is lower, peer conformity will be higher. The contribution of self-control to peer conformity among female students who consume electronic cigarettes (vapes) in Bandung City is 34.8%. Abstrak. Work Engagement. Konformitas teman sebaya pada mahasiswa wanta yang mengkonsumsi rokok elektrik (vape) di Kota Bandung masih terbilang tinggi, salah satu penyebabnya adalah rendahnya tingkat self-control. Self-control adalah kemampuan kognitif yang membantu dinamika pembentukan suatu perilaku pada individu, rendahnya self-control dapat berdampak pada ketidakmampuan individu untuk menentukan suatu perilaku dari berbagai pilihan alternatif yang ada seperti konformitas teman sebaya pada mahasiswa wanita yang mengkonsumsi rokok elektrik (vape) di Kota Bandung.Penelitian ini menggunakan pendekatan kuantitatif dengan metode korelasional dan menggunakan covenience sampling. Subjek penelitian ini adalah 103 mahasiswa wanita yang mengkonsumsi rokok elektrik (vape) di Kota Bandung. Pengumpulan data pada penelitian ini menggunakan alat ukur Self Control Scale (SCS) yang tellah yang dibuat olelh Averill (1973) yang telah diadaptasi olelh Nabila (2020) dan The Conformity Scale (TCS) yang dibuat olelh Sears et al.(2009) yang tellah diadaptasi olelh Jessica (2017). Hasil analisi data menyatakan bahwa terdapat hubungan negatif signifikan antatara self-control dan konformitas teman sebaya dengan nilai r = -0,544 dan p = 0,000. Artinya semakin tinggi self-control maka sakan semakin rendah konformitas teman sebaya, dan sebaliknya apabila self-control semakin rendah maka akan semakin tinggi konformitas teman sebaya. Adapaun kontribusi self-control dengan konformitas teman sebaya pada mahasiswa wanita yang mengkonsumsi rokok elektrik (vape) di Kota Bandung sebesar 34,8